How should we intervene in psychosis risk syndromes - Wang, Jijun; Jiang, Kaida; Zhang, Tianhong; Li, Huijun; Woodberry, Kristen; Seidman, Larry (Shanghai Jingshen Yixue, 2013)
Summary： Research diagnostic instruments such as the Structured Interview for Prodromal Syndromes （SIPS） are now able to reliably identify individuals with different types of psychosis risk syndromes （PRS）. About one-third of individuals with PRS convert to a diagnosable psychotic disorder within three years of the initial assessment. Currently available randomized controlled trials of interventions aimed at reducing the rate of psychotic conversion of PRS are promising, but they are too small and too short in duration to provide definitive conclusions about effectiveness. Given the high level of false positives （i.e., most individuals with PRS do not progress to frank psychosis） and the lack of definitive evidence about effectiveness, we recommend a staged approach to intervention in PRS that only uses antipsychotic medication after other, more benign approaches have been tried. At present the best approach appears to be to develop high-quality case- management systems for individuals with PRS that provide close follow-up, psychoeducation and psychosocial support to patients and family members, and, possibly, psychotherapeutic and pharmacological treatments （with antipsychotic medications or neuroprotective agents）. The effectiveness of these proposed interventions needs to be tested in large randomized controlled trials that follow up subjects for at least three years.